Refugees, membership, and state system legitimacy. Issue 4 (2nd October 2022) - Buxton, Rebecca; Draper, Jamie
Abstract: In the literature on refugeehood in political theory, there has been a recent turn towards what have been called "state system legitimacy" views. These views derive an account of states' obligations to refugees from a broader picture of the conditions for international legitimacy. This paper seeks to develop the state system legitimacy view of refugeehood by subjecting the most developed version of it—the account developed by David Owen—to critical scrutiny. We diagnose an ambiguity in Owen's theory of refugeehood, in the concept of political membership, and unpack the implications of this ambiguity for state system legitimacy views. First, we reconstruct the key aspects of Owen's account of refugeehood and show how it represents an advance over competing theories. Then we discuss the methodological underpinnings of Owen's account, showing the constraints and opportunities faced by state system legitimacy views. Next, we raise some problems for the conceptual distinctions that Owen develops between different types of refugee protection: asylum, sanctuary, and refuge. The underlying feature that leads to these problems is an ambiguity in the concept of political membership, which is at the core of Owen's view of refugeehood. Finally, we distinguish two interpretations of political membership in the institution of refugeehood and chart out some possible ways forward for state system legitimacy views. The critique developed here is a sympathetic one, aimed at the further development of state system legitimacy views.